Health on Radio: A Study of ‘Ultimate Health’ On Joy Fm and ‘Healthline’ On Uniiq Fm. - Kwarteng, A. B. (University of Ghana, 2016)
A healthy nation is a national asset. Thus in Ghana where the doctor to patient ratio is 1 to 10,452, there is the need to have health information dissemination avenues where patients can get basic health information without travelling to the hospital or clinic. Radio with its ubiquity and mobility as well as being the most pervasive medium in Ghana, stand as the best medium to help bridge this gap. There is therefore the need to examine the content on radio to ascertain whether the health information disseminated is beneficial and useful to the end user. This study therefore sought to investigate the content of health on radio, focusing on the categories of topics and issues covered the structure and elements of health messages broadcasted and the reasons for the selection of topics and experts who serve as discussants on selected topics. Employing content analysis and in-depth interviews, the findings indicate that majority of topics were on public health (59.4%) issues, followed by specific diseases (37.5%) with health policy and systems (3.1%) receiving the least of coverage. Follow-up information was adequately provided on Ultimate Health (eight out of ten) but not on health Line. Also, both programmes focused equally on prevention, treatment, detection, causes and advances in research. Consistent with previous literature, all the topics had expert(s) discussants as Health practitioners should harnessing the dissemination of public health education through radio since health content on radio in Ghana does not deviate much from the literature.
Theses (M. A.) - University of Ghana, 2016